Role of Magnetic Resonance Imaging and Ultrasonography in Evaluation of Chronic Non osseous Shoulder Pain. - Abdelrahman Hassan; Mostafa Shakweer; Ahmed Ashour; Ahmed Abo Rashid (International Journal of Medical Arts, 2021)
Background: Chronic shoulder pain is a common clinical presentation. It is of osseous or non-osseous origin. In non-osseous shoulder pain, proper diagnosis is critical. Magnetic resonance imaging [MRI] is the standard diagnostic modality. However, it is expensive and not available in many medical centers. Thus, the availability of cheap alternative is crucial. Aim of the work: The current research aimed to assess the diagnostic performance of ultrasonography versus conventional MRI in different causes of chronic non-osseous shoulder pain. Patients and Methods: Fourty patients with chronic shoulder pain due to different causes were participated in the current work. They were selected from Al-Azhar University Hospital [Damietta]. All were assessed on clinical basis [history, physical examination and laboratory investigations]. Then, all were submitted to radiological investigations [Plain X-ray, shoulder ultrasound, and Magnetic resonance imaging]. The diagnostic value of ultrasound was estimated versus that of magnetic resonance imaging. Results: by ultrasound, tendinosis was reported in 55.0%, partial thickness tear in 27.5%, articular surface in 20.0%, full thickness tear in 12.5%, bursal surface [7.5%], neoplastic [2.5%] and infraspinatus tendon full thickness tear [2.5%]. Ultrasound able to diagnose supraspinatus tendinopathy [91.7%], full thickness complete tear [83.3%], supraspinatus impingement [85.3%], subacromial subdeltoid bursitis [92.0%] and long head biceps tenosynovitis [84.2%]. Otherwise, ultrasound specificity is over its sensitivity power for partial thinness tear on articular [80.0%] or bursal surfaces [85.3%], full thickness complete tear [94.1%], shoulder joint effusion [92.3%], LHB tenosynovitis [85.7%] and labral tears [100.0%]. Conclusion: Shoulder ultrasound could be considered as a reasonable alternative to magnetic resonance imaging in the diagnosis of different causes of chronic shoulder pain. However, its value widely different from condition to another. Thus, it could be used as a rapid screening tool, and the use of MRI could be ascribed for specific conditions [cases with lower ultrasound sensitivity].